Simultaneous Determination of Eight Bioactive Compounds in Dianthus superbus by High-performance Liquid Chromatography - Yun, Bo-Ra (Pharmacogn Mag, 2016)
BACKGROUND: Dianthus superbus, one of traditional herbal medicine, is widely used to treat urethritis, carbuncles and carcinoma. OBJECTIVE: A simultaneous determination method was established for controlling the quality of D. superbus using the eight compounds, (E)-methyl-4-hydroxy-4-(8a-methyl-3-oxodecahydronaphthalen-4a-yl) (1), diosmetin-7-O(2'',6''-di-O-α-L-rhamnopyranosyl)-β-D-glucopyranoside (2), vanillic acid (3), 4-hydroxyphenyl acetic acid (4), 4-methoxyphenyl acetic acid (5), (E)-4-methoxycinnamic acid (6), 3-methoxy-4-hydroxyphenylethanol (7), and methyl hydroferulate (8) isolated from D. superbus. MATERIALS AND METHODS: This analysis method was developed using high performance liquid chromatography coupled with diode array detector with a Shishedo C(18) column at a column temperature of 3°C. The mobile phase was composed of 0.1% trifluoroacetic acid in water and acetonitrile. The flow rate was 1 ml/min and detection wavelength was set at 205 nm and 280 nm. Validation was performed in order to demonstrate selectivity, accuracy and precision of the method. RESULTS: The calibration curves showed good linearity (R(2) > 0.99). The limits of detection and limits of quantification were within the ranges 0.0159–0.6205 μg/ml and 0.3210–1.8802 μg/ml, respectively. Moreover, the relative standard deviations of intra- and inter-day precision were both <2.98%. The overall recoveries were in the range of 96.23–109.87%. Quantitative analysis of eight compounds in 12 D. superbus samples (D-1–D-12) from various regions were analyzed and compared by developed method. CONCLUSION: As a result, this established method was accurate and sensitive for the quality evaluation of eight compounds isolated from D. superbus and may provide a new basis for quality control of D. superbus. SUMMARY: A simultaneous determination method of eight compounds in Dianthus superbus was established by high performance liquid chromatography-diode array detector. Developed analysis method is validated with linearity, precious and accuracy. The newly established method was successfully evaluated contents of eight compounds in 12 D. superbus samples (D.1.D.12) from various regions and compared. Abbreviations used: HPLC: High performance liquid chromatography, LOD: Limits of detection, LOQ: Limits of quantification, RSD: Relative standard deviation.